2018
DOI: 10.3390/polym10111292
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Properties of Novel Polyurethanes Containing Long-Segment Fluorinated Chain Extenders

Abstract: In this study, novel biodegradable long-segment fluorine-containing polyurethane (PU) was synthesized using 4,4′-diphenylmethane diisocyanate (MDI) and 1H,1H,10H,10H-perfluor-1,10-decanediol (PFD) as hard segment, and polycaprolactone diol (PCL) as a biodegradable soft segment. Nuclear magnetic resonance (NMR) was used to perform 1H NMR, 19F NMR, 19F–19F COSY, 1H–19F COSY, and HMBC analyses on the PFD/PU structures. The results, together with those from Fourier transform infrared spectroscopy (FTIR), verified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 37 publications
0
31
0
Order By: Relevance
“…For example, PU 0-90-10 was synthetized using 0% w/w of PEG, 90% w/w of PCL, and 10% w/w of PE. A theoretical HS content was calculated based on the equation described by Lee et al [9], which relates the number of isocyanate and chain extenders to the number of total components. HS was assumed to be IPDI and PE.…”
Section: Synthesis Of Polyurethanesmentioning
confidence: 99%
“…For example, PU 0-90-10 was synthetized using 0% w/w of PEG, 90% w/w of PCL, and 10% w/w of PE. A theoretical HS content was calculated based on the equation described by Lee et al [9], which relates the number of isocyanate and chain extenders to the number of total components. HS was assumed to be IPDI and PE.…”
Section: Synthesis Of Polyurethanesmentioning
confidence: 99%
“…The mechanical properties of PU are mainly determined by the degree of microphase separation during PU formation. Microphase separation is generated by the polarity between hard and soft segments, which also causes the clustering of hard segments [17,18]. The formation of microphase separation mainly arises from the generation of hydrogen bond between the -NH group on urethane group (–COONH–) hard segment and C=O group, which promotes the aggregation of hard segment.…”
Section: Introductionmentioning
confidence: 99%
“…A study revealed that high uorine content in PU indicated a high level of microphase separation of PU, and elevated tensile strength. 29 Most relevant studies have examined uorinated PU by changing the content of uorinated chain extenders; changing the ratio of so segment content to uorinated chain extender content may result in different ratios of so segments to hard segments, which may affect the properties of PU. 30 To our knowledge, no research has discussed, with a constant R value (NCO : OH), the inuence of uorine on PU; therefore, the present study changed the chain length of a uorinated chain extender to investigate the effect of such length on PU.…”
Section: Introductionmentioning
confidence: 99%